2018
DOI: 10.1016/j.scitotenv.2018.04.153
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability in orchards after land transformation: Consequences for precision agriculture practices

Abstract: The change from traditional to a more mechanized and technical agriculture has involved, in many cases, land transformations. This has supposed alteration of landforms and soils, with significant consequences. The effects of induced soil variability and the subsequent implications in site-specific crop management have not been sufficiently studied. The present work investigated the application of a resistivity soil sensor (Veris 3100), to map the apparent electrical conductivity (ECa), and detailed multispectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…As for yield mapping, production maps provide useful information for fruit growers. Fruit orchards usually show spatial variability due to soil variations, fertility, water irrigation, among others (Uribeetxebarria et al, 2018). An analysis of yield maps helps farmers to find the reasons for such variability and to determine which areas of lower productivity require special attention.…”
Section: Introductionmentioning
confidence: 99%
“…As for yield mapping, production maps provide useful information for fruit growers. Fruit orchards usually show spatial variability due to soil variations, fertility, water irrigation, among others (Uribeetxebarria et al, 2018). An analysis of yield maps helps farmers to find the reasons for such variability and to determine which areas of lower productivity require special attention.…”
Section: Introductionmentioning
confidence: 99%
“…Tree fruit differs from most annual crops in that plants are clonal, suggesting that there should be minimal variability between them compared with annual crops. However, orchard management and site-specific soil and climate effects accumulated over the years lead to significant within-orchard spatial variability that influences yield [11,12]. In this context, remote sensing could improve the efficiency of ground sampling protocols for yield assessments by (i) identifying the exact number of bearing trees in the orchard and (ii) detecting the spatial variability using auxiliary variables such as the Normalized Difference Vegetation Index (NDVI) or crown size [3] so that precision agriculture (PA) techniques would aid in classifying trees into homogeneous zones, which constitute sampling strata, lowering the MSS required.…”
Section: Introductionmentioning
confidence: 99%
“…In agriculture, many authors have shown that remote sensing and vegetation indexes such as Red Vegetation Index (RVI) or NDVI were correlated with the spatial variation of tree characteristics and yield [11][12][13][14][15][16]. However, contributions attempting to apply remote sensing in sampling designs are recent and mostly focused mostly in viticulture.…”
Section: Introductionmentioning
confidence: 99%
“…This is an important task in PA because it supposes the identification of areas within a field with different productive potential, allowing the opportunity for differential management to be assessed [7][8][9].…”
Section: Introductionmentioning
confidence: 99%